Determinants of Exclusive Breastfeeding Among Mothers with Infants Aged 6–24 Months: Exclusive Breastfeeding Among Mothers with Infants Aged 6–24 Months - Ratih Wirapuspita Wisnuwardani; Siti Nur Aini; Ismail Kamba; Reny Noviasty; Erri Larene Safika (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2026)
Background : Exclusive breastfeeding during the first six months of life is essential for optimal infant growth, development, and disease prevention. However, the coverage of exclusive breastfeeding remains below national and regional targets in many areas of Indonesia Objective : This study aimed to analyze the determinants of exclusive breastfeeding among mothers with infants aged 6–24 months in the working area of Puskesmas Waru, Penajam Paser Utara Regency, East Kalimantan Province. Methods : An observational analytic study with a cross-sectional design was conducted among 122 mothers selected using simple random sampling from a population of 345 mothers. Data were collected using structured questionnaires measuring maternal knowledge, maternal attitude, early initiation of breastfeeding (IMD), maternal occupation, family support, health worker support, and exclusive breastfeeding practices. Data were analyzed using Chi-square tests with a significance level of α = 0.05. Results : The results showed that 44.3% of mothers practiced exclusive breastfeeding, while 55.7% did not. Maternal knowledge (p = 0.000), maternal attitude (p = 0.000), and family support (p = 0.000) were significantly associated with exclusive breastfeeding. In contrast, maternal occupation (p = 0.875) and health worker support (p = 0.083) were not significantly associated with exclusive breastfeeding Conclusions : These findings indicate that behavioral and social factors play important roles in influencing exclusive breastfeeding practices. Strengthening health promotion programs that improve maternal knowledge, foster positive breastfeeding attitudes, and enhance family involvement is essential to increase exclusive breastfeeding coverage.